Explaining the Effectiveness Model of IFRS Adoption on Components of Professional Ethics through Job Attitudes: From the Perspective of Certified Public Accountants in the Iranian Association of Certified Public Accountants - Ebrahimi Athar, Taleb; Jafari Dehkordi, Hamidreza; Banitalebi Dehkordi, Bahareh (Management Strategies and Engineering Sciences, 2025)
The main objective is to explain the effectiveness of IFRS on the components of professional ethics through the job attitudes of certified public accountants. The present study is a causal-comparative application in terms of purpose. The statistical population of the study is all certified public accountants active in Iranian association of certified public accountants, of which 371 were selected as a simple random sample using the Cochran formula. In this study, commitment, enthusiasm, and job trust were considered as the job attitudes of certified public accountants. Also, five components of confidentiality, honesty, independence, competence, and professional conduct were used to measure professional ethics. A questionnaire was used to measure the research variables. The validity and reliability of the research questionnaires were approved. Finally, data analysis was performed using structural equations using AMOS software. Using confirmatory factor analysis, the convergent validity of each of the variables in the proposed model was approved. The results also showed that the implementation and acceptance of IFRS has a significant positive effect on the job attitudes of certified public accountants. Job commitment and enthusiasm have a significant effect on the components of professional ethics of certified public accountants. Job trust has a significant effect on the components of professional ethics of accountants (except competence). Finally, the results of the Sobel test showed that IFRS has a significant effect on the components of professional ethics through job attitudes (except professional conduct and professional competence).